ClC-3 Expression and Its Association with Hyperglycemia Induced HT22 Hippocampal Neuronal Cell Apoptosis - Feiyan Fan; Tao Liu; Xin Wang; Dongni Ren; Hui Liu; Pengxing Zhang; Zhen Wang; Nan Liu; Qian Li; Yanyang Tu; Jianfang Fu (Journal of Diabetes Research)
Although apoptosis plays an important role in the development of Diabetic Encephalopathy (DE), the underlying molecular mechanisms remain unclear. With respect to this, the present work aims to study the variation in chloride/proton exchanger ClC-3 expression and its association with HT22 hippocampal neuronal apoptosis under hyperglycemic condition in vitro. The cells were stimulated with added 0, 5, or 25 mM glucose or mannitol for up to 72 hours before assessing the rate of ClC-3 expression, cell viability, and apoptosis. In a consecutive experiment, cells received chloride channel blocker in addition to glucose. The rate of cellular death/apoptosis and viability was measured using Flow Cytometry and MTT assay, respectively. Changes in ClC-3 expression were assessed using immunofluorescence staining and western blot analysis. The results revealed a significant increase in cellular apoptosis and reduction in viability, associated with increased ClC-3 expression in high glucose group. Osmolarity had no role to play. Addition of chloride channel blocker completely abolished this effect. Thus we conclude that, with its increased expression, ClC-3 plays a major role in hyperglycemia induced hippocampal neuronal apoptosis. To strengthen our understanding of this aforesaid association, we conducted an extensive literature search which is presented in this paper.